Some biological and genomic properties of rice tungro bacilliform badnavirus and rice tungro spherical waikavirus from Nepal - Dahal, G.; Druka, A.; Burns, T.M.; Villegas, L.C.; Fan, Z.; Shrestha, R.B.; Hull, R. (1996)
A survey of rice fields during the main growing seasons in 81 locations from 21 districts of the southern Terai region of Nepal indicated that rice tungro was primarily restricted to the Hardinath (Janakpur) and (Parwanipur (Bara) regions. The tungro incidence in Hardinath ranged from 17% to 51% and in Parwanipur from 6% -61% causing about 89% grain yield loss in Hardinath. Both rice tungro bacilliform badnavirus RTBV) and rice tungro spherical picornavirus(RTSV) were found in tungro isolates collected from Hardinath and Parwanipur. These isolates were transmitted by Nephotettixvirescens and leaf extracts reacted to antisera against (TRBV) and (RTSV). In a dot blot hybridization assay, leaf extract of 12 weed species collected from the tungro affected area in Hardinath and Parwanipur also reacted with RTBV DNA probes. On mass inoculation of 15 porpular rice cultivars most became more than 50% infected and onlycv. Rad 9 had low (22.2%) infection. RTBV DNA and the coat protein region of RTSV from the Hardinath isolate were cloned and partially characterized. A comparative analysis by restriction endonuclease digestion, cross hybridization, the polymerase chain reaction and partial sequencing indicated that the Nepalese RTBV DNA clone and the cDNA clones of the RTSV RNAwere more similar to the various tungro isolates from the Indian subcontinent than to those from the Philippines.